Historical and generational forces in the Iridescent Life Course of bisexual women, men, and gender diverse older adults. (January 2022) - Fredriksen Goldsen, Karen; Jen, Sarah; Clark, Theresa; Kim, Hyun-Jun; Jung, Hyunzee; Goldsen, Jayn
Purpose: Little is known about the life course of bisexual older adults. This study examines life events and experiences of bisexuals by generation: Pride Generation, born 1950–1964; Silenced Generation, born 1935–1949; and Invisible Generation, born 1934 or earlier, as well as by gender among women, men, and gender diverse older adults. Methods: Aging with Pride: National Health, Aging, and Sexuality/Gender Study is the first national longitudinal study of LGBTQ older adults in the US. We utilize the Iridescent Life Course to examine the life events and life course experiences of bisexual older adults ( N = 216) using 2014 survey data. The Iridescent Life Course frames this study for comparing generational and gender differences in five key areas: identity development; work; kin and social relationships; bias-related experiences; and physical and mental health. Findings: The Invisible Generation, the oldest generation, compared to the two younger generations, reports significant risks related to social relationships, the lowest levels of openly disclosing, and fewer bias-related experiences. They also demonstrate important signs of resilience and better mental health. Bisexual men and gender diverse older adults report higher rates of bias-related experiences and fewer social resources than bisexual women. Conclusion: Based on the Iridescent Life Course, we document important differences in the heterogeneity and intersectionality in bisexual lives, particularly for those in late life and those gender diverse. It is essential to document the distinct nature of bisexuals' life course, as it provides both historical and contemporary insights into aging and the reframing of future research.